Three-dimensional kinematics and power output in elite para-kayakers and elite able-bodied flat-water kayakers - Bjerkefors, A.; Rosén, J. S.; Tarassova, O.; Arndt, A. (Journal of Applied Biomechanics, 2019)
Trunk, pelvis, and leg movements are important for performance in sprint kayaking. Para-kayaking is a new Paralympic sport in which athletes with trunk and/or leg impairment compete in 3 classification groups. The purpose of this study was to identify how physical impairments impact on performance by examining: differences in 3-dimensional joint range of motion (RM) between 10 (4 females and 6 males) elite able-bodied kayakers and 41 (13 females and 28 males) elite para-kayakers from the 3 classification groups, and which joint angles were correlated with power output during high-intensity kayak ergometer paddling. There were significant differences in RM between the able-bodied kayakers and the 3 para-kayak groups for the shoulders (flexion, rotation: able-bodied kayakers<para-kayakers); trunk and pelvis (rotation: able-bodied kayakers>para-kayakers); and legs (hip, knee, and ankle flexion: able-bodied kayakers>para-kayakers) during paddling. Furthermore, athletes with greater impairment exhibited lower trunk and leg RM compared with those with less impairment. Significant positive correlations were observed for both males and females between power output and peak shoulder and trunk flexion; trunk and pelvis rotation RM; and hip, knee, and ankle flexion RM. This information is important for understanding how key kinematic and kinetic variables for para-kayaking performance vary between athletes from different classification groups.